A comparison of two methods of endoscopic dilation of acute subglottic stenosis using a ferret model1234. (7th September 2012) - Tubbs, Kyle J.; Silva, Rodrigo C.; Ramirez, Harvey E.; Castleman, William L.; Collins, William O.
Abstract: Objectives/Hypothesis: Balloon dilation is accepted as a first line treatment of acute subglottic stenosis, but its effects on the subglottic tissue remain largely unknown. We aimed to develop an animal model of acute subglottic stenosis using endoscopic techniques. Once developed, this model was used to compare the immediate effects of balloon dilation and endotracheal tube dilation on subglottic tissue. Study Design: Prospective randomized animal study. Methods: Acute subglottic injury was induced in 10 ferrets by endoscopic cauterization with silver nitrate. After 48–72 hours of observation, eight animals were randomized to undergo subglottic dilation with either a 5‐mm balloon or endotracheal tubes of increasing diameter. These eight ferrets were euthanized within 10 minutes after dilation. The other two ferrets served as controls and were euthanized following observation only. The larynx from each ferret was harvested, and the subglottis was examined histologically by a pathologist blinded to the treatment arms. Results: Acute subglottic stenosis was induced in all 10 ferrets using the endoscopic technique. Both balloon and endotracheal tube dilation resulted in comparable improvement in the subglottic airway diameter. A decreased thickness of submucosa/lamina propria was seen in the balloon dilation group. Conclusions: Acute subglottic stenosis can be reliably induced in ferrets using endoscopic techniques. Multiple dilation methods can be used to relieve acute obstruction. Balloon dilators seem to improve airway patency, in part, by decreasing the thickness of the submucosa and lamina propria. Further research is needed to determine how this impacts later stages of wound healing and final outcomes. Laryngoscope, 2013